Fly-Fishing on Vimeo: Cas(t)ing the Channel. Issue 1 (2nd January 2017) - Fennell, David
ABSTRACT: This article explored the symmetry of characteristics and practices that define meaning and identity of fly anglers using Bourdieu's theory of habitus. Content analysis was used to analyze a systematic random sample of videos ( N = 260) that anglers posted on Vimeo in relation to characteristics, fishing behavior, parallel actions, and content. Results confirmed that several key dispositions were shared within the videos, including type of water fished (rivers), type of fish caught (Salmonids), gratuitous lift of caught fish out of water, catch-and-release, treatment of fish once caught, the place of video (North America), and language of video (English). Suggestions are made to advance social science research in this area.